BASIC BIOMECHANICAL CHARACTERIZATION OF POLYURETHANE BASED ARTIFICIAL CANCELLOUS STRUCTURES - Jan Šleichrt; Daniel Kytýř; Kateřina Pithartová; Sascha Senck; David Fürst; Andreas Schrempf (Acta Polytechnica CTU Proceedings, 2018)
The main goal of this study is to validate elementary mechanical parameters of a newly designed open-cell foam. The purpouse for investigating artificial material is to approach the properties of the human bone in the case of its adequate replacement. Investigated material can be also used as an artificial bone to train surgical procedures and to improve the skills of the surgeons. Four sets of the foam with different chemical composition were subjected to an uniaxial quasi-static loading to describe basic mechanical behaviour of these samples. Based on these experiments, the stress-strain diagrams were created as a comparative tool including calculation of the effective Young’s modulus. The acquired knowledges will be used as input parameters of a follow-up study aimed at describing the morphology of presented structures and their response to mechanical experiments. A distortion effect of porosity on the results is not considered in this study.